DINAMIKA PERKEMBANGAN BATIK KLASIK - Dharsono (Sony Kartika) (Institut Seni Indonesia Surakarta, 2011)
Batik is a painting or drawing which is made by using a tool called â€œcantingâ€ (a copper vessel with a spouted nib) on a white cambric. A person painting, drawing or writing on a white cambric using canting is called membatik (to do batik work). Doing batik work produces a batik work having a variety of motifs with special characteristics. The emergence of hand-blocked batik (batik cap), although it is not as soft as hand-drawan batik, can keep traditional values existing in hand â€“drawn batik alive. Hand-blocked batik reproduces previosly prohibited batik works. After that, it is not waxing process in batik that is speeded up but drawing motifs and colouring so that cloth with batik motif which is really similar to batik. This batik cloyh is called â€œbatik printingâ€ (hand-blocked batik).The dynamic of batik development diverts batik consumers. People swift to batik motif textile while Indonesian bourgeois class wear hand drawn batik cloth in the interest of formal occasions or parties. The dynamics will take hand-drawn batik to an exclusive throne. Then batik becomes a source of glorification and then it will be a philosophical exemplar and the source of inspiration to make and develop batik further.Â According to Javanese culture, batik is not only esthetically pleasing but the motif of classical batik also become a guidance (principle). That is why, batik is the great work ofÂ Indonesian people and now it has been acknowledged as the tangible and intangible heritage of the world.Keywords: batik,canting,printing